Vote or adstain the effect of repetitive exposure and type of advertisement on the inclination to vote for a presidential candidate - Cadiz, Dominique (Dunong: UP Diliman Journal of Student Research, 2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Dunong/article/view/8814/7772